Histone deacetylase 6’s function in viral infection, innate immunity, and disease: latest advances - Qu, Min; Zhang, Huijun; Cheng, Pengyuan; Wubshet, Ashenafi Kiros; Yin, Xiangping; Wang, Xiangwei; Sun, Yuefeng (Frontiers in Immunology, 2023)
In the family of histone-deacetylases, histone deacetylase 6 (HDAC6) stands out. The cytoplasmic class IIb histone deacetylase (HDAC) family is essential for many cellular functions. It plays a crucial and debatable regulatory role in innate antiviral immunity. This review summarises the current state of our understanding of HDAC6's structure and function in light of the three mechanisms by which it controls DNA and RNA virus infection: cytoskeleton regulation, host innate immune response, and autophagy degradation of host or viral proteins. In addition, we summed up how HDAC6 inhibitors are used to treat a wide range of diseases, and how its upstream signaling plays a role in the antiviral mechanism. Together, the findings of this review highlight HDAC6's importance as a new therapeutic target in antiviral immunity, innate immune response, and some diseases, all of which offer promising new avenues for the development of drugs targeting the immune response.